Identifikasi Penyebab Keterlambatan pada Departemen Injection Molding Machine PT. XYZ - Magda F. D. N. R. B. Duarte (Jurnal Titra, 2018)
PT. XYZ has a problem with finish good delivery to the custsomer. The identification of delay is done by analysing one process at PT. XYZ, called Injection Molding Machine (IMM). Based on the result of analysing data is discovered that delay at IMM its affected by 2 factor. That factors is delaying of actual start production and actual leatime that taken longer than basic. Identification of 2 factor that has affected on delay is done by using 5-why analysis. This method is using to find the real root cause of the factors. The result of analysis is discovered that the real root cause of delaying actual start production is causing by the line up of production. While, the real root cause of actual leadtime that taken longer than baisc is causing by the interrupted of other production process, downtime, (mold and process), speed gap and  reject product.